2016
DOI: 10.1177/1744259116672437
|View full text |Cite
|
Sign up to set email alerts
|

Pore-size distribution effects on the thermal conductivity of the fired clay body from lightweight bricks

Abstract: This study investigated the effects of three pore-forming agents on the properties of the fired clay body applied in the production of lightweight bricks for the building envelopes. Test samples were made from clay raw material already containing two combustible pore-forming agents (sawdust and cellulose sludge). A part of this research was focused on studying the influence of adding two combustible pore-forming agents (molasses and cornstarch) and a chemical additive Vuppor to the claw raw material. Testing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…A qualitative measure of the macroporosity is provided in Figure , and a quantitative analysis of porosity is provided in Table . Considering both macro and meso porosity analyses in this study, our data supports the conclusions of Sveda et al in that the brick containing wood ash had both increased porosity and increased thermal conductivity compared to the base brick. However, decoupling the effects of pore size distribution and type of residual remaining after firing, was not accomplished in this study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A qualitative measure of the macroporosity is provided in Figure , and a quantitative analysis of porosity is provided in Table . Considering both macro and meso porosity analyses in this study, our data supports the conclusions of Sveda et al in that the brick containing wood ash had both increased porosity and increased thermal conductivity compared to the base brick. However, decoupling the effects of pore size distribution and type of residual remaining after firing, was not accomplished in this study.…”
Section: Resultssupporting
confidence: 90%
“…The porosity of the brick will reduce its thermal conductivity. However, the size and type of porosity in the brick may matter . Nagy et al found that 10 and 50 μm pores resulted in the same reduction in thermal conductivity, but the smaller pores resulted in much greater compressive strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was most likely related to the structure of the pores (which were smaller in size and distributed uniformly) and the excellent densification process at 770 °C, indicating the importance of the selected sintering temperature. The relationship between pore size/distribution/amount and thermal conductivity has been previously reported for silica ceramics [ 43 , 44 ]. The experimental and theoretical research results showed that pore size, especially, is a decisive influencing factor in the thermal properties products [ 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 83%
“…The relationship between pore size/distribution/amount and thermal conductivity has been previously reported for silica ceramics [ 43 , 44 ]. The experimental and theoretical research results showed that pore size, especially, is a decisive influencing factor in the thermal properties products [ 43 , 44 , 45 ]. On the other hand, the highest value, of 3.955 W/K.m, was obtained for the G12BN@770 sample, which is consistent with the reported high density, low porosity, and improved microstructure of the sample.…”
Section: Resultsmentioning
confidence: 83%